Application of Procedures in Processing Vendor Bill Payments PT PLN (PERSERO) UP3 BALI Timur - Ni Putu Shri Ayu Wulan Devi; Putu Sri Arta Jaya Kusuma (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Work Practice was out for two months at PT PLN UP3 Bali Timur. PLN is a BUMN in the energy sector and has 11 subsidiaries that support the company's performance and services. The PLN subsidiary is engaged in the generation, electricity supply, telecommunications, finance, and maintenance services. Placed in the Finance section and carry out activities related to verification of vendor bill payment files carried out by PT. PLN Bali Section until the payment of the trade payables is made. In carrying out fieldwork practices, there are several benefits such as increased knowledge and insight regarding the procedure for paying business debts at PT PLN UP3 Bali Timur and experience not obtained in college. The trade payable payment procedures that have been implemented, such as the related sections, and the documents used, are mostly by on the existing theory. But the stages of the bill payment procedure at each company are very important to pay attention to so that the stages of the payment procedure run according to good procedures. Efforts are made to improve the Payment Bill Procedure steps so that vendors are more thorough and not careless in completing the required files, but apart from that, all payment procedures regarding accounts payable at PT. PT PLN UP3 Bali Timur has been carried out according to the procedure.